Students’ Perceptions of Literary Texts, Challenges in Learning, and Learning Strategies - Soy, Seth; Maisarah, Ira; Sovann, Ly (Institut Agama Islam Negeri Kudus, 2023)
Students’ perceptions are very crucial for improving the quality of teaching and learning. However, the study of students’ perceptions of learning literature is very limited. Therefore, this study aims to explore EFL students’ perceptions of literary texts, challenges in learning literature, and out-of-class learning strategies. The study applied the descriptive quantitative method. The stratified random sampling technique was also employed. The samples (n = 122) were the EFL students at the National University of Battambang. The online survey questionnaire was used as the research instrument with the Likert scale of four choices (strongly disagree, disagree, agree, and strongly agree). The data was analyzed automatically by Google Forms. Three main results were revealed. First, the majority of students have positive perceptions of the literary text used in their class (76,61%), although some viewed vocabulary and grammatical structures as complicated elements. Second, although most of the students do not face many challenges in learning literature (62,38%), a large number of students believed that text difficulty, workload from other classes, and poor English proficiency cause difficulties for them. Third, despite the majority of students having better learning strategies (72.02%), a specific learning schedule, task completion before class, and learning discussion between peers are the learning activities that the rest of the students failed to implement. In conclusion, the literary texts are appropriate despite a few problematic aspects that might be accordingly adapted. Also, the teachers should pay attention to learners’ challenges and suggest better learning strategies to them.